ADAPTING TO THE CHALLENGES OF THE 21st CENTURY FOOD AND AGRICULTURE - Singh Dhiman, Jagtar; Pratibha, (International Journal of Psychosocial Rehabilitation, 2021)
Environmental change has become one of the world's most major problems as of late, influencing individuals, the climate, and the economy. Because of the need to increase worldwide food supply under the decreasing accessibility of soil and water assets and the rising dangers from environmental change, farming will confront huge difficulties in the 21st century. There are chances to make food and work frameworks that are stronger to natural, financial, and social dangers due to these challenges. These difficulties require the utilization of current multidisciplinary information as well as the advancement of an assortment of new mechanical and institutional developments. Environmental change is difficult for agribusiness and agrarian arrangement making, just like the evolving environment. As the impacts of environmental change are supposed to decline, horticulture should figure out how to lessen its ozone-harming substance emanations (GHGs). In a discussion given to the MIT Enterprise Forum in 2003, Nobel laureate Richard E. Smalley illustrated humanity's Top Ten Problems for the Next 50 Years. Teacher Smalley accepts that the most major problems confronting humankind today are energy, water, food, the climate, destitution, psychological oppression, and battle, as well as illnesses, instruction, a vote-based system, and populace development. An outline of the significant difficulties confronting the worldwide food and horticultural framework in the 21st century, as well as the effects of environmental change, is one of the objectives of this review. It expects to sum up key discoveries about a portion of these issues. Environmental change difficulties (dry spell, cold, saltiness) and their effect on farming will be the focus of future review studies.